The invention of party politics : federalism, popular sovereignty, and constitutional development in Jacksonian Illinois - Leonard, Gerald Flood (Studies in legal history., 2002)
This work uncovers the constitutional foundations of that most essential institution of modern democracy, the political party. It rejects the view that Martin Van Buren and other Jacksonian politicians had the idea of a modern party system in mind when they built the original democratic system.